Where Have all the Flowers Gone? : The Diary of Molly Mackenzie Flaherty - White, Ellen Emerson (New York, NY : Scholastic, 2002)
In 1968 Massachusetts, after her brother Patrick goes to fight in Vietnam, fifteen-year-old Molly records in her diary how she misses her brother, volunteers at a Veterans' Administration Hospital, and tries to make sense of the war in Vietnam and the tumultuous events in the United States. Includes historical notes.
Keywords: Vietnamese Conflict, 1961-1975 -- Fiction -- United States; Vietnamese Conflict, 1961-1975 -- Fiction -- United States; Nineteen sixties -- Fiction; Brothers and sisters -- Fiction; Diaries -- Fiction; United States -- Fiction -- History -- 1961-1969; United States -- Fiction -- History -- 1961-1969; Boston (Mass.) -- Fiction